Snižování rizika pokročilé investiční strategie - Budík, Jan; Smolíková, Lenka (Univerzita Pardubice, 2013)
The article deals with the issue of advanced investment strategies and reduces their risk by using the orders for automatically closing the open position at a loss for a pre-defined value. The advantage of strategies that do not use these protective orders is that they can survive against the price movement and then close the position at a profit. The disadvantage is that the open positions are subject to unlimited risk because of the use of financial leverage. The aim of this paper is to eliminate the risk of open-ended losses while maintaining the potential profitability of these strategies. This statistical analysis is used to test the large number of combinations of levels to close the position at a loss. Using this analysis is to find the optimal value for closing a position at a loss, which currently does not reduce profitability. The article compares the results of the proposed portfolio without the use of protection orders and the use of protective orders for the period 2005 - 2012. The results of this analysis show the need for the use of protection orders in the use of financial leverage. Analyzed strategy works in intraday mode, where the purchase made at 17:00 and 22:00 in the case of sales made to meet the entry conditions.
Risk reduction of advanced investment strategy
Keywords: currency; risk; investment strategy; optimization; reduction